Probing the cumulative effects of unit operations and lactose to whey protein ratios on protein modifications in powdered model infant formula. (September 2022) - Lund, Pernille; Mardal, Freja; Ray, Colin A.; Lund, Marianne N.
Abstract: The impact of lactose to whey protein ratio on processed-induced protein modifications was investigated in powdered model infant formula. Model samples were prepared with different lactose to whey protein ratios and different total protein concentrations; protein modifications were evaluated before, during and after processing. Lab-scale equipment was used to mimic commercial manufacturing, and a powdered young-child formula was included to elucidate cumulative effects of commercial unit operations. Maillard-related and structural protein modifications were affected differently by unit operations, both in model samples and commercial formula. Maillard reaction products (furosine, α-dicarbonyls and advanced glycation end products) increased with increased lactose content of model samples, whereas absence of lactose facilitated formation of disulphide-linked aggregates, lysinoalanine and lanthionine. The lowest level of protein modifications was observed at a 30:70 lactose to whey protein ratio, suggesting partial dry blending of lactose as a feasible approach to improve protein quality in powdered infant formula.